Protected and unprotected W-W-W connection at elevated temperatures - Aissa, Abderrahim (2018)
The wood, as a structural material, continues to grow far beyond traditional applications. Connections are often considered as the critical point of timber structures because their resistance and durability mainly depend on the joining design in structural elements. For imposed thermal loads, it remains important to improve the knowledge of the connection behaviour under ﬁre